Analisis Perhitungan Anggaran dan Insentif pada Karyawan Sarang Burung Walet Surabaya - Siska Wulandari; Lis Setyowati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study is to analyze the calculation of direct wages and incentives at the company. This type of research uses qualitative research. Data obtained from interviews and several documents from the company. Data collection techniques used are documentation and interviews. The results of this study use the direct labor budget theory, to determine the calculation of direct wages and incentives.The benefits of this study explain the calculation of direct wages and incentives for companies.